The Role of Regional / City Governments in Developing and Supervising Of Village Regulation - Adhe Ismail Ananda; Sri Kusriyah (Jurnal Daulat Hukum, 2020)
The research objective was to identify and analyze the role of district / city government in the guidance and supervision of village regulations. This research method is a normative-empirical approach, by examining Laws and regulations related to the role of district / city local governments in fostering and supervising village regulations with their implementation. The conclusions from the results of this study indicate that in the formation of a Village Regulation, the role of district / city Regional Government is regulated in Article 115 of Act No. 6 of 2014 concerning Villages, one of which is to provide guidelines for drafting village regulations and village head regulations. The technical guidelines for the preparation of village regulations in Kolaka district are regulated in Perda No. 4 of 2009 in its implementation the technical guidelines are still very difficult to adjust to the current conditions due to the issuance of the Law of Permendagri No. 6 of 2014 concerning the Village.Keywords: Coaching; Supervision; Regional Government; Village Regulations; Regent Regulation.